Dicliptera Chinensis polysaccharides target TGF-Î²/Smad pathway and inhibit stellate cells activation in rats with dimethylnitrosamine-induced hepatic fibrosis - Zhang, X; Zhang, J; Jia, L; Xiao, S (Cellular and Molecular Biology, 2016)
This study aims to study impact of Dicliptera chinensis polysaccharide (DCP) on hepatic fibrosis (HF) and activation of hepatic stellate cells (HSCs). Liver fibrosis model was induced by intraperitoneal injection of dimethyl nitrosamines (DMN) in rat. Rats in treatment group were administrated with different concentrations of DCP (0, 100, 300 mg/kg) by intraperitoneal injection. Hematoxylin and eosin (H&E) and Masson's trichrome staining were used to assess histo-pathological change. Î±-SMA, TGF-Î²1 and pSmad 2/3 were assayed by immuno-histochemistry. HSC-T6 cells were stimulated by recombined rat TGF-Î²1 (1 ng/mL) to simulate an activating model in vitro and then interfered with DCP (concentration of 0, 25, 50, 100, 200, 400 µg/ml). MTT assay was used to determine cell proliferation and western blotting was used to detect Î±-SMA and pSmad 2/3 expression. Results demonstrated that DCP alleviated DMN-induced liver fibrosis in rat and significantly down-regulated TGF-Î²1 expression, pSmad2/3 and Î±-SMA in liver tissue in a dose-dependent way. DCP inhibited proliferation and activation of TGF-Î²1-stimulated HSC-T6 in vitro and significantly down-regulated Î±-SMA and pSmad2/3 expression. In conclusion, this study revealed that DCP attenuates progression of liver fibrosis through suppressing TGF-Î²/Smad pathway. DCP is a potential botanical polysaccharide to management liver fibrosis.